Characterization of The Main Characters in The Kissing Booth Movie - Septiarini , Komang Nindya Dewi; Utami , Ni Made Verayanti; Juniartha , I Wayan (Institut Pariwisata dan Bisnis Internasional, 2024)
This study conducted to deal with two research method problems which are (1) What are the characterization of the main characters in the movie The Kissing Booth. Qualitative method was used to analysed the data in this study. To answer the first and the second problem this study applied the theory from Halliday (1999). The discussion is focused on two main characters, namely Elle Evans and Noah Flynn. The data source was a movie entitled The Kissing Booth. The data were collected through library research by watching the movie, reading script, and note taking. The result of this study shows that are four aspects of characterization of the main characters. In showing those aspects, the writer presented the picture or dialogue from the movie. There were four aspects of characterization analysed by the writer, there are physical appearance, personality, social status, and social relationship.